2008
DOI: 10.1002/pits.20307
|View full text |Cite
|
Sign up to set email alerts
|

Role of reading engagement in mediating effects of reading comprehension instruction on reading outcomes

Abstract: The engagement model of reading development suggests that instruction improves students' reading comprehension to the extent that it increases students' engagement processes in reading. We compared how Concept-Oriented Reading Instruction (CORI) (support for cognitive and motivational processes in reading), strategy instruction (support for cognitive strategies in reading), and traditional instruction in fourth-grade classrooms differentially influenced students' reading comprehension, strategy use, and engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
159
0
23

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(189 citation statements)
references
References 15 publications
7
159
0
23
Order By: Relevance
“…A child who values reading wants to explore various literacy situations, and has reasons to use reading in a meaningful way. (Brozo, Shiel, & Topping, 2008;Wigfield & Barbosa, 2008.) As was mentioned above, boys' reading skills are not as good as girls' skills and girls succeed better than boys in every area of literacy.…”
Section: Reading Attitudesmentioning
confidence: 98%
“…A child who values reading wants to explore various literacy situations, and has reasons to use reading in a meaningful way. (Brozo, Shiel, & Topping, 2008;Wigfield & Barbosa, 2008.) As was mentioned above, boys' reading skills are not as good as girls' skills and girls succeed better than boys in every area of literacy.…”
Section: Reading Attitudesmentioning
confidence: 98%
“…According to V. Vaish (2016) and Wigfield et al (2008) the term 'engagement' as a goal of teaching reading is consistent with a multi-dimensional approach in that it includes behavioral, emotional/motivational, and cognitive aspects. Thus, the engaged reader is assumed to be behaviorally active (reading frequently), internally motivated (liking to read), and cognitively active (uses strategies in reading).…”
Section: Introductionmentioning
confidence: 99%
“…The central pursuit of a recent innovative content approach, Concept-Oriented Reading Instruction (CORI), which was developed by Guthrie and Wigfield (2000), is to foster an in-depth understanding of the conceptual content of the text through the avenue of active engagement of the student. Extensive research has revealed that CORI interventions have positive effects on reading motivation and reading comprehension compared to approaches that are based on traditional or mere strategy instruction (Guthrie and Klauda 2014;Guthrie, McRae, and Klauda 2007;Guthrie et al 2004;Wigfield et al 2008).…”
Section: Introductionmentioning
confidence: 99%